Is it feasible to construct a community profile of exposure to industrial air pollution?. Issue 8 (1st August 2000) - Pless-Mulloli, Tanja; Dunn, Christine E; Bhopal, Raj; Phillimore, Peter; Moffatt, Suzanne; Edwards, John
Abstract : OBJECTIVE: An epidemiological investigation to assess the validity of residential proximity to industry as a measure of community exposure. METHODS: 19 Housing estates in Teesside (population 1991: 77 330) in north east England were grouped into zones: A=near; B=intermediate; C=further from industry. With residential proximity of socioeconomically matched populations as a starting point a historical land use survey, historical air quality reports, air quality monitoring, dispersion modelling data, and questionnaire data, were examined. RESULTS: The populations in zones A, B, and C were similar for socioeconomic indicators and smoking history. A reas currently closest to industry had also been closest for most of the 20th century. Historical reports highlighted the influence of industrial emissions to local air quality, but it was difficult to follow spatial pollution patterns over time. Whereas contemporary NOx and benzene concentrations showed no geographical variation, dispersion modelling of emissions (116 industrial stacks, traffic, and domestic sources) showed a gradient associated with industry. The presumed exposure gradient of areas by proximity to industry (A>B>C) was evident for all of zone A and most of zones B and C. CONCLUSIONS: It was feasible to assemble a picture of community exposure by integration of measurements from different sources. Proximity of residence was a reasonable surrogate for complex community exposure.